Internet panderism from the perspective of Islamic jurisprudence - Ã˜Â§Ã›ÂŒÃ˜Â²Ã˜Â¯Ã›ÂŒ Ã™ÂÃ˜Â±Ã˜Â¯, Ã˜Â¹Ã™Â„Ã›ÂŒ Ã˜Â§ÃšÂ©Ã˜Â¨Ã˜Â±; Ã˜ÂÃ˜Â³Ã›ÂŒÃ™Â† Ã™Â†ÃšÂ˜Ã˜Â§Ã˜Â¯, Ã˜Â³Ã›ÂŒÃ˜Â¯ Ã™Â…Ã˜Â¬Ã˜ÂªÃ˜Â¨Ã›ÂŒ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Internet panderism, in todayâs society, is a crime which, due to technological advances, has spread significantly and perhaps, in comparison to traditional panderism, it causes far more losses. Since it is unprecedented, the ruling of internet panderism has not been considered even by contemporary Islamic jurists. After mentioning some examples of internet panderism and a detailed review, the authors have relied on arguments such as the conduct of wise and basis emendation to prove that internet panderism is a crime. They have, finally, invoked the absoluteness of Abd Alla Ibn Sanan tradition and basis emendation and concluded that since the requirements of panderism with prescribed punishment (haddi panderism) are satisfied in such panderism, internet procurers will be punished by prescribed punishment (had) of panderism, if they bring individuals together with the intention that they commit illegitimate acts of adultery and sodomy.